Targeting macrophage polarization by Nrf2 agonists for treating various xenobiotics-induced toxic responses. (13th June 2021) - Wang, Yi-Ran; Zhang, Xiu-Ning; Meng, Fan-Ge; Zeng, Tao
Abstract: Macrophages can polarize into different phenotypes in response to different microenvironmental stimuli. Macrophage polarization has been assigned to two extreme states, namely proinflammatory M1 and anti-inflammatory M2. Accumulating evidences have demonstrated that M1 polarized macrophages contribute to various toxicants-induced deleterious effects. Switching macrophages from proinflammatory M1 phenotype toward anti-inflammatory M2 phenotype could be a promising approach for treating various inflammatory diseases. Studies in the past few decades have revealed that nuclear factor erythroid 2-related factor 2 (Nrf2) can modulate the polarization of macrophages. Specifically, activation of Nrf2 could block M1 stimuli-induced production of proinflammatory cytokines and chemokines, and shift the polarization of macrophages toward M2 by cross-talking with nuclear factor kappa-B (NF-κB), mitogen-activated protein kinases (MAPKs), peroxisome proliferator-activated receptor γ (PPARγ), and autophagy. Importantly, a great number of studies have confirmed the beneficial effects of natural and synthesized Nrf2 agonists on various inflammatory diseases; however, most of these compounds are far away from clinical application due to lack of characterization and defects of study designs. Interestingly, some endogenous Nrf2 inducers and compounds with dual activities (such as the Nrf2 inducing and CO releasing effects) exhibit potent anti-inflammatory effects, which points out an important direction for future researches.